Pendampingan Komunitas melalui Upaya Membangun Karakter Enterpreneurship pada Pengurus Bank Sampah Songlikoer di Masa Pandemi COVID-19 - Mawasti, Wahanani; Alvini, Egi; Wahyuni, Sri; Budiono, Tri Djoyo (Proceedings of Annual Conference on Community Engagement, 2022)
The COVID-19 pandemic has impacted on various activities, including the activities of the Waste Bank. The COVID-19 pandemic  reduced the revenue of the Songolikoer Garbage Bank, both due to a decrease in the number of customers and a decrease in the price of waste. The many challenges of developing a Waste Bank during the pandemic require an increase in the capacity of the Waste Bank management, in the form of an entrepreneurial mentality and mindset. As a form of university service to the community, socialization, and assistance activities are carried out to build entrepreneurial character for the Songolikoer Waste Bank management. The goal is that the management has an entrepreneurial character and can implement these characteristics in the Waste Bank. Community service activities were carried out through socialization, FGD, and personal assistance to the Songolikoer Waste Bank management, both bravely and face to face. This activity was able to foster the spirit of entrepreneurship in the management of the Songolikoer Waste Bank. The entrepreneurial spirit is manifested concretely in the form and marketing of creative products from waste recycling. As well as providing benefits in the form of increasing the income of the Waste Bank during the Covid-19 Pandemic.